Renal and Blood Pressure Response to a High-Salt Diet in Mice With Reduced Global Expression of the Glucocorticoid Receptor - Ivy, Jessica R.; Evans, Louise C.; Moorhouse, Rebecca; Richardson, Rachel V.; Al-Dujaili, Emad A. S.; Flatman, Peter W.; Kenyon, Christopher J.; Chapman, Karen E.; Bailey, Matthew A. (Frontiers in Physiology, 2018)
Salt-sensitive hypertension is common in glucocorticoid excess. Glucocorticoid resistance also presents with hypercortisolemia and hypertension but the relationship between salt intake and blood pressure (BP) is not well defined. GRβgeo/+ mice have global glucocorticoid receptor (GR) haploinsufficiency and increased BP. Here we examined the effect of high salt diet on BP, salt excretion and renal blood flow in GRβgeo/+mice. Basal BP was ∼10 mmHg higher in male GRβgeo/+ mice than in GR+/+ littermates. This modest increase was amplified by ∼10 mmHg following a high-salt diet in GRβgeo/+ mice. High salt reduced urinary aldosterone excretion but increased renal mineralocorticoid receptor expression in both genotypes. Corticosterone, and to a lesser extent deoxycorticosterone, excretion was increased in GRβgeo/+ mice following a high-salt challenge, consistent with enhanced 24 h production. GR+/+ mice increased fractional sodium excretion and reduced renal vascular resistance during the high salt challenge, retaining neutral sodium balance. In contrast, sodium excretion and renal vascular resistance did not adapt to high salt in GRβgeo/+ mice, resulting in transient sodium retention and sustained hypertension. With high-salt diet, Slc12a3 and Scnn1a mRNAs were higher in GRβgeo/+ than controls, and this was reflected in an exaggerated natriuretic response to thiazide and benzamil, inhibitors of NCC and ENaC, respectively. Reduction in GR expression causes salt-sensitivity and an adaptive failure of the renal vasculature and tubule, most likely reflecting sustained mineralocorticoid receptor activation. This provides a mechanistic basis to understand the hypertension associated with loss-of-function polymorphisms in GR in the context of habitually high salt intake.